Commensal Staphylococci attenuate Staphylococcus aureus skin colonization and inflammation via AHR-dependent signaling - Riebelmann, Jule; Kienzle, Nicole; Sauer, Birgit; Schittek, Birgit (Frontiers in Immunology, 2025)
IntroductionStaphylococcus aureus is the leading cause of bacterial skin infections in several inflammatory skin diseases, however, is rarely detected on healthy skin. Skin barrier defects, such as in atopic dermatitis, promote S. aureus colonization by yet unknown mechanism. In our previous work we found that in healthy skin commensal staphylococci including Staphylococcus epidermidis and Staphylococcus lugdunensis (SL) protect against S. aureus skin colonization, however, the microbiome-mediated protection is lost in inflammatory skin. Here, we investigated how microbiome-derived factors contribute to skin defense under homeostatic and inflammatory conditions.MethodsWe examined how bacterial conditioned media (BCM) from S. epidermidis and S. lugdunensis influence immune responses in primary human keratinocytes, human skin explants, and 3D skin reconstructs. Immune signaling was assessed using LEGENDplex cytokine profiling, RT2 Profiler PCR arrays, and western blotting. To investigate how BCM pretreatment limits S. aureus colonization, we performed inhibitor studies with a focus on aryl hydrocarbon receptor (AHR) signaling. The effects of BCM under inflammatory conditions were analyzed in tape-stripped human skin explants and 3D skin models with an atopic dermatitis–like phenotype.ResultsWe show that released factors from SE and SL reduce S. aureus skin colonization by inducing antimicrobial peptides (AMPs) and suppressing inflammatory responses in the skin. Both, factors released by SE and SL, limit S. aureus-induced immune activation in the skin by dampening inflammatory signaling, reducing reactive oxygen species, and suppressing expression of danger-associated molecular patterns (DAMPs). We show that this anti-inflammatory effect is mediated by activation of aryl hydrocarbon receptor (AHR) signaling in keratinocytes. Mechanistically, SE and SL membrane vesicles are involved in activating AHR signaling in keratinocytes via direct vesicle-cell contact as well as by bacterial tryptophan metabolites. This protective effect is lost in inflamed skin, where it instead exacerbated inflammation due to impaired AHR activity in inflamed skin. Interestingly, co-treatment of human AD-like skin equivalents with released SE factors together with an AHR ligand effectively reduces S. aureus colonization pointing out a potential novel AHR- and microbiome-based therapeutic strategy in AD.DiscussionTogether, these findings highlight a context-dependent role of microbiome-derived factors in shaping cutaneous immunity and underscore the therapeutic potential of restoring AHR signaling to enhance the skin’s defense against S. aureus, particularly in inflammatory disorders such as AD.